New Facile Synthesis of 3,4-Dihydroquinazoline-2(1H)-thiones by a Sequential Ugi-Azide/Staudinger/Aza-Wittig/Cyclization Reaction - Xiong, Jun; Min, Qing; Yao, Gang; Zhang, Jia-An; Yu, Hai-Feng; Ding, Ming-Wu (Synlett, 2019)
A new facile synthesis of 3,4-dihydroquinazoline-2(1H)-thiones by an Ugi-azide/Staudinger/aza-Wittig/cyclization sequence has been developed. The Ugi-azide reactions of 2-azidobenzaldehydes, amines, trimethylsilyl azide, and isocyanides produced tetrazoles, which, when treated with methyldiphenylphosphane and CS2, produced 3,4-dihydroquinazoline-2(1H)-thiones in good overall yields via a sequential Staudinger/aza-Wittig/cyclization reaction.
Keywords: 3,4-dihydroquinazoline-2(1H)-thione; Ugi-azide reaction; methyldiphenylphosphane; aza-Wittig reaction; cyclization reaction